A new modification of the homotopy perturbation method. (July 2021) - Yunbunga Adamu, Magaji; Ogenyi, Peter
This study proposes a new modification of the homotopy perturbation method. A new parameter alpha is introduced into the homotopy equation in order to improve the results and accuracy. An optimal analysis identifies the parameter alpha, aimed at improving the solutions. A comparative analysis of the proposed method reveals that the new method presents results with higher degree of accuracy and precision than the classic homotopy perturbation method. Absolute error analysis shows the convenience of the proposed method, providing much smaller errors. Two examples are presented: Duffing and Van der pol's nonlinear oscillators to demonstrate the efficiency, accuracy, and applicability of the new method.